2013
DOI: 10.1179/1607845412y.0000000044
|View full text |Cite
|
Sign up to set email alerts
|

Pure red cell aplasia associated with cytomegalovirus and Epstein–Barr virus infection in seven cases of Chinese children

Abstract: Pure red cell aplasia (PRCA) associated with cytomegalovirus (CMV) and Epstein-Barr virus (EBV) infection is uncommon. Here, we describe the clinical features and management of seven cases of Chinese children with PRCA associated with viral infections. The patients presented with pallor on admission. Blood cell counts and marrow smears showed anemia, reticulocytopenia, and aplasia of erythroblasts. Serological investigation and DNA polymerase chain reactions for CMV were positive in four patients and those te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…10,31 PRCA can also be associated with viral infections, such as EBV, CMV, 54 and human parvovirus B19. 55 In a large case series of PRCA in CLL (n=30), parvovirus testing was performed in 24 patients and was noted to be positive in 6 (25%) patients.…”
Section: Pure Red Cell Aplasiamentioning
confidence: 99%
“…10,31 PRCA can also be associated with viral infections, such as EBV, CMV, 54 and human parvovirus B19. 55 In a large case series of PRCA in CLL (n=30), parvovirus testing was performed in 24 patients and was noted to be positive in 6 (25%) patients.…”
Section: Pure Red Cell Aplasiamentioning
confidence: 99%
“…The generation of these antibodies in patients on immunosuppressants is thought to occur through immune dysregulation . Although CMV could be a potential cause of PRCA in this patient, the timing of the PRCA and the absence of significant viremia, which have been described in other cases, make CMV less likely …”
Section: Discussionmentioning
confidence: 74%
“…PRCA occurring in association with AIHA has been reported in association with hepatitis A, immunosuppressive therapy, lupus, lymphoma, Sjogren's syndrome, CMV, and EBV infection and in children with no underlying medical problems . The interval between onset of PRCA and AIHA varies widely from simultaneous occurrence to 4 years between PRCA and AIHA .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of question (2), several antivirals, including rituximab, have been used for a number of conditions; for example, cases of uveitis (valganciclovir),47 interstitial pneumonitis with pancytopenia (acyclovir),48 cutaneous amyloidosis (acyclovir),49 vasculitis (eg, of CNS and or eye—acyclovir),50 51 keratoconjunctivitis (acyclovir),52 interstitial nephritis (acyclovir),53 erythema multiforme (acyclovir),54 acute retinal necrosis (acyclovir),55 transverse myelitis (ganciclovir),56 oesophagitis (acyclovir),57 epithelial cell tumours and haematological malignancies(ganciclovir),58 59 other malignancies (cidofovir)60 and other blood dyscrasias (ganciclovir) 61. A 2010 review reported favourable outcomes of antiviral treatment in most immunocompetent patients with severe manifestations (mainly neurological: meningoencephalitis, cerebellitis, Guillain-Barre, facial nerve palsy, myeloradiculitis) in which antivirals had been used (mainly acyclovir, along with steroids) 62.…”
Section: Discussionmentioning
confidence: 99%